ORAL MEDICATIONS IN PATIENTS SUFFERING FROM ACUTE LOW BACK PAIN- NARRATIVE REVIEW (Journal of Pharmaceutical Negative Results, 2022)
Low back pain, whether with or without sciatica, is usually self-limiting and does not indicate a major underlying condition. Reassurance, pain medicines, and encouragement to stay active are usually enough for most people. In some patients, "red flag" abnormalities linked to an elevated risk of cauda equina syndrome, malignancy, infection, or fracture necessitate a more thorough examination. These patients will also require more frequent monitoring and, in certain situations, an immediate referral to a surgeon. Imaging can be postponed for at least four to six weeks in individuals with nonspecific mechanical low back pain, allowing the discomfort to subside. Acetaminophen, nonsteroidal antiinflammatory medications, skeletal muscle relaxants to stay active have all been shown to be useful. When compared to sham therapy, spinal manipulation therapy may produce short-term improvements, but not when compared to standard treatments. The natural history of back pain, its overall favorable prognosis, and treatment suggestions should be the emphasis of patient education.